2020
DOI: 10.4317/medoral.23630
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of traumatic dental injury in Valencia, Spain

Abstract: Background While traumatic dental injuries (TDI) are an increasingly frequent occurrence in everyday dental practice, little research on TDIs has been published in Spain. The aim of this study was to determine the incidence of TDIs in a population in Valencia (Spain) and investigate influential variables. In addition, a protocol for TDI data collection is proposed. Material and Methods This retrospective study compiled data from patients attending a private dental clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
4
2
0
Order By: Relevance
“…According to the collected data, males suffered more TDIs than females (m: n = 342, female: n = 236). This correlates with previous findings of published literature [ 13 , 14 , 15 ] and agrees with studies that attribute a higher risk of TDIs to gender and age. Authors have postulated that males have a greater propensity towards contact sports and risky behavior than girls [ 6 , 16 ].…”
Section: Discussionsupporting
confidence: 93%
“…According to the collected data, males suffered more TDIs than females (m: n = 342, female: n = 236). This correlates with previous findings of published literature [ 13 , 14 , 15 ] and agrees with studies that attribute a higher risk of TDIs to gender and age. Authors have postulated that males have a greater propensity towards contact sports and risky behavior than girls [ 6 , 16 ].…”
Section: Discussionsupporting
confidence: 93%
“…Although not in the same order, these reasons have been previously reported. 24,36 Falls and automobile accidents had more severe sequels than recreational activity and violence, which is in agreement with previous literature reports.…”
Section: Discussionsupporting
confidence: 92%
“…Although some studies did not find sex-based differences, 23 in general it has been observed that boys are more likely to suffer TDI in permanent dentition than girls. 24 Most explanations for such difference seem to be ascribed to stereotypical perspectives about practice of sports, so that males are preferentially engaged in physical contact sports than females. 25 Girls might also tend to avoid risky behaviors, thereby reducing incidence of traumatic injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, our results are in agreement with a recent epidemiological study, which identified a comparable prevalence (13%) of dental traumas [27]. However, the present results might be different in comparison to those based on clinical examination in patients with isolated dental injuries [28,29].…”
Section: Discussionsupporting
confidence: 89%